Economic Knowledge Production of the Growing New Farmers Consortium, 2000-2005: A Critical Discourse Analysis of Adult Agricultural Education - Kim Niewolny; Arthur Wilson (Adult Education Research Conference, 2007)
This study is a critical discourse analysis of adult education material developed by the Growing New Farmers Consortium (GNFC) from 2000 through 2005. Findings illustrate GNFC’s role in (re)producing the privileged tradition of neoliberal marketization existing more broadly in adult agricultural education.